Dydaktyka literatury jako nauka = Literature Didactics as a Science - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper demonstrates the independence of literature didactics and what it is based on as a branch which has just been developing as a seperate science. A connection is shown between literature didactics and other sciences such as the theory of literature, psychology, praxiology, general didactics and aesthetics
Keywords: dydaktyka literatury; nauka